EMPLOYEE PERFORMANCE MEASUREMENT ANALYSIS USING THE BALANCE SCORE CARDS - Budiyono Budiyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to determine the balance scorecard measurement from the perspective of finance , customers , internal business processes , growth and learning have a partial effect on the performance of employees of Bank Negara Indonesia. from the perspective of partial influence on the performance of employees of Bank Negara Indonesia. The scope taken in this study is a survey conducted on research respondents, namely employees of Bank Negara Indonesia. The type of data in this study is Qualitative data in the form of questionnaires and research location data. While the second data is quantitative data in the form of data from respondents' questionnaires that have been quantified. The results in this study are that there is a partial influence on the measurement of the balance scorecard from the perspective of finance , customers, business processes, and learning and Keywords: Performance, employee, balanced score, card